Value of natriuretic peptides and tissue Doppler imaging in the estimation of left ventricular filling pressure in patients with cardiac amyloidosis - Didier Carrié; Stéphanie Brun; Eve Cariou; Pauline Fournier; David Ribes; Stanislas Faguer; Antoine Huart; Michel Galinier; Daniel Adoue; Laurent Alric; Léonardo Astudillo; Pauline Bernadet Monrozies; et al. (Open Heart)
Background Estimation of left ventricular filling pressures (LVFP) is a determining factor in the follow-up of patients with cardiac amyloidosis (CA). Natriuretic peptides (NPs) and tissue Doppler imaging may be used to monitor LVFP in patients with CA. The aim of this study was to evaluate the value of NPs and Doppler parameters in estimating LVFP in patients with CA.Methods Fifty patients with biopsy-verified light chain (n=31), A protein amyloidosis (AA) (n=1), apoliporotein A2 (n=1) or bone scintigraphy-proven transthyretin (n=17) CA were retrospectively included. All patients underwent right heart catheterisation (RHC). Among them, 48 (96%) and 43 (86%) had assays of NPs (20 brain natriuretic peptide (BNP), 27 N-terminal pro-hormone brain natriuretic peptide (NT-proBNP) and 1 both) and transthoracic echocardiography performed within 24 hours of RHC, respectively.Results The median BNP and NT-proBNP levels were 1000 (243–1477) ng/L and 10 106 (2935–13 348) ng/L, respectively. Echocardiography demonstrated left atrial enlargement with a mean volume of 47±16 mL and low tissue Doppler lateral Ea of 5±2 cm/s. The mean early diastolic mitral inflow velocity on early lateral mitral annular diastolic velocity ratio (E/Ea) ratio was 18±7, and the mean pulmonary capillary wedge pressure (PCWP) by RHC was 18±8 mm Hg. There was no correlation between BNP (r=0.260, p=0.774) or NT-proBNP (r=−0.103, p=0.984) levels and PCWP. There was a slight correlation between E/Ea ratio and PCWP (r=0.337, p=0.029). E/Ea ratio >14 performed poorly in differentiating elevated and low LVFP.Conclusion In patients with CA, NPs do not accurately estimate PCWP. Tissue Doppler-derived mitral E/Ea ratio is correlated with PCWP, but the slight correlation requires to estimate LVFP in a broad clinical and imaging context to avoid diagnostic errors.